1996
DOI: 10.1051/rnd:19960205
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural demonstration of glucose-6-phosphatase activity and glycogen in skeletal muscles of newborn piglets with the splayleg syndrome

Abstract: Summary -The ultrastructural localization of glucose-6-phosphatase activity and glycogen were investigated in the longissimus dorsi and biceps femoris muscles of normal and splaylegged newborn piglets. Significant differences were ascertained in the distribution of the reaction product of glucose-6-phosphatase activity between the two groups of animals. A fine precipitate was found in the sarcoplasmic reticulum and in the perinuclear cisternae of normal piglet muscles. In splaylegged muscles, variable deposits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…In addition, RAB32 was also highlighted as an important potential gene regulating lipid metabolism [55]. Ultrastructural analysis of the muscle of PSL and normal piglets (longissimus dorsi and biceps femoris) clearly demonstrated that mitochondria were often located near the sarcolemma of the normal piglets, but presented within the sarcoplasm of the PSL, which resulted in the increased accumulation of glycogen in the muscles of PSL [11]. It should be noted that glycogen is the first energy store in the piglet at birth.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, RAB32 was also highlighted as an important potential gene regulating lipid metabolism [55]. Ultrastructural analysis of the muscle of PSL and normal piglets (longissimus dorsi and biceps femoris) clearly demonstrated that mitochondria were often located near the sarcolemma of the normal piglets, but presented within the sarcoplasm of the PSL, which resulted in the increased accumulation of glycogen in the muscles of PSL [11]. It should be noted that glycogen is the first energy store in the piglet at birth.…”
Section: Resultsmentioning
confidence: 99%
“…Histomorphological investigations described PSL as myofibrillar hypoplasia, however, which was not exclusive to PSL as this condition was also found in clinically normal piglets [10]. In addition, ultrastructural analysis of PSL muscles clearly demonstrated an increased accumulation of glycogen compared with the muscles of normal piglets [11]. Besides the histological studies, the expression of the atrophy marker FBXO32 highly increased in PSL muscles (semitendinosus, longissimus dorsi, and gastrocnemius muscles) [4].…”
Section: Introductionmentioning
confidence: 99%
“…The cause of the PSL might relate to the abnormal glycogen metabolism [ 14 ]. Compared to the normal pigs, muscle fiber reduction and glycogen accumulation were observed in the longitudinal and transvers section of PSL pigs’ muscle tissues [ 20 ]. The distribution of glucose-6-phosphatase’s metabolites in longissimus dorsi and biceps femoris muscle were significant differences between PSL and normal pigs [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Compared to the normal pigs, muscle fiber reduction and glycogen accumulation were observed in the longitudinal and transvers section of PSL pigs’ muscle tissues [ 20 ]. The distribution of glucose-6-phosphatase’s metabolites in longissimus dorsi and biceps femoris muscle were significant differences between PSL and normal pigs [ 20 ]. Although there is no direct evidence that ARNT involved in regulating the glucose metabolism, it can form a heterodimer mixture with HIF-1α and HIF-2α which could affect the skeletal muscle type and glycogen metabolism [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, they found that increased blood glucose and lower hemoglobin levels in SL pigs weighing less than 1 kg allowed for a greater transmission of macromolecules from sow colostrum. Antalikova et al (1996) added to this effort and reported that ultrathin sections of muscles from SL pigs had fewer myofibrils and greater accumulation of glycogen within the extramyofibrillar spaces than muscles of normal pigs.…”
Section: Discussionmentioning
confidence: 99%